Transfer pricing or formula apportionment?: tax-induced distortions of multinationals' investment and production decisions - Jan Thomas Martini; Rainer Niemann; Dirk Simons (Center for Economic Studies and ifo Institute (CESifo), 2007)
For mitigating the problems of transfer pricing formula apportionment (FA) is discussed intensively. However, FA could even be more harmful than transfer pricing because income shifting would require changing economic decisions instead of just taking advantage of accounting options. We analyze the impact of different international tax allocation regimes on a corporate group's investment and production decisions. We show that FA offsets the advantages of decision decentralization as it reverses the separation of responsibilities. It is not clear whether FA is desirable from a fiscal or an entrepreneurial perspective. The effects of FA compared to transfer pricing depend strongly on the parameter setting under consideration, especially the decision procedure within corporate groups.
Keywords: H25; G21; M41; 330; Doppelbesteuerung; Transferpreis; Formula Apportionment; Steuerwirkung; Multinationales Unternehmen; Direktinvestition; Besteuerungsgrundsatz; Theorie